Dysregulation of endocrine disruption, apoptosis and the transgenerational toxicity induced by spirotetramat. (February 2020) - Zhang, Jie; Qian, Le; Wang, Chen; Teng, Miaomiao; Duan, Manman; Zhou, Yimeng; Chen, Xiangguang; Bo, Rui; Wang, Chengju; Li, Xuefeng
Abstract: Spirotetramat (SPT) is a new tetronic acid derivative insecticide used to control scales and aphids; the potential for endocrine disruptor effects in fish could not be finalized with the available data. In this study, zebrafish were selected to assess the endocrine-disrupting effects. Significant decrease of plasma estradiol (E2), testosterone (T) and 11-ketotestosterone (11-KT) were observed in both male and female following the spirotetramat exposure; the vitellogenin (VTG) level in females significantly decreased. The expression of the hypothalamic-pituitary-gonad (HPG) axis genes fshr, lhr and esr1 showed significant increase in the gonads, which expression in males is higher than in females. In addition, the activities of capspase-3 and caspase-9 significantly decreased in both males and females liver, while the capspase-3 and caspase-9 were increased in male testis, the mRNA expression levels of genes expression related to the apoptosis pathway were also significantly altered after the spirotetramat exposure. Additionally, we found the parental zebrafish exposed to spirotetramat induced the development delay of its offspring. Above all, the adverse effects induced by spirotetramat suggesting that spirotetramat is a potential exogenous hazardous agent. Graphical abstract: Image 1 Highlights: Spirotetramat interfering with zebrafish endocrine system. Spirotetramat could reduce zebrafish plasma E2, T and VTG level and induced 11-KT. Spirotetramat could induce apotosis in zebrafish gonads. Parental exposure to spirotetramat caused zabrafish offspring development delayed.